Framework for strengthening primary health care and community networks to mitigate the long-term psychosocial impact of floods in Kerala. (January 2021) - Kiran, P.S.; Mohan, Bindu; Abhijith, V.; Abraham, Amal; Anoop, G.; Dinesh, R.S.; Krishnan, Hareesh; Mahadevan, Krishna; Peethambaran, Manju; Kunheen, Marwa; Sidharthan, Midhun; Prathibha, S.; et al.
Abstract: Individuals who encounter disasters experience negative consequences across physical, mental and psychosocial domains. Impacts on mental health and psychosocial domains are more common, and last longer than physical health problems. In August 2018, the state of Kerala, India witnessed unprecedented floods that resulted in 483 deaths and significant loss of property and livelihood. Project "PARIRAKSHA" was implemented by the Government of Kerala, to mitigate the long-term psychosocial impact of the disaster. It has been one of the largest comprehensive post-disaster psychosocial project in India till date, aimed to benefit approximately 2 million people across 93 panchayats which experienced severe flooding and loss of life. This paper describes the detailed methodology of this project. In addition, the supplementary material includes the technical manuals that were prepared, and is freely accessible to personnel in disaster affected zones. Counsellors were newly appointed in all the primary health centres in affected panchayats to provide mental health and psychosocial support. Accredited Social Health Activists (community level health workers) undertook home-visits to ensure early case-detection. Medical officers' in affected areas received booster training regarding pharmacological management of mental health issues. Multi-disciplinary mobile mental health teams were constituted to ensure availability of specialised mental health inputs locally. The project integrated additional mental health resource personnel, into the existing health care system. Existing health care personnel received training to improve competency in dealing with post-disaster psychosocial issues. This framework is expected to ensure early detection and intervention, thus facilitating timely psychosocial recovery of communities impacted by the floods. Highlights: Kerala, India witnessed unprecedented floods in 2018. The disaster led to large scale of loss of life and property. To facilitate psychosocial recovery a large psychosocial project was launched. This paper describes the detailed methodology of the project.